PERBEDAAN PENGARUH METODE PEMBELAJARAN MASSED PRACTICE DAN DISTRIBUTED PRACTICE TERHADAP KEMAMPUAN LOB BULUTANGKIS DITINJAU DARI POWER OTOT LENGAN ( Studi Eksperimen Pada Pemain Putra Tingkat Pemula Persatuan Bulutangkis Purnama Surakarta) - RENY ARDHIANINGRUM (Universitas Tunas Pembangunan, 2015)
THEDIFFERENT INFLUENCE OF LEARNING METHOD MASSED PRACTICE AND DITRIBUTED PRACTICE FOR ABILITY OF BADMINTON LOB OBSERVATION OF ARM MUSCLE(Surakarta Purnama Association Badminton Study Experiment for Man Player Level Beginner). Purpose of observation to knowing (1) Different influence ofÂ Â learning method with massed practice and distributed practice for badminton lob abilityfor man player level beginner. (2) Different badminton lob abilitybetween who have good the arm power muscle, medium arm muscle power and less arm muscle power for man player badminton level beginner. (3) There are or not influence interaction between learning method and arm muscle power for badminton lob ability for man player badminton level beginner. This research use experiment method composed three variable, there are free variable manipulation (learning method massed practice and distributed practice), attributive variable (arm muscle power) and bunch variable (lob blow). Plan of research is 2x3 factorial. Sample used in this research is badminton athlete level beginner Surakarta Purnama Badminton Association with 59 of child sample total. Sample interpretation use purposive random sampling. Data of power arm muscle got with throw softball ball test (Distance Throw Test), and than ability of lob measured with ability lob blow test. Technique data analysis use ANAVA. Before examine with ANAVA, beforehand use sample normalitas test (Lillifors test with Î±=0.05) and homogenitas varians test (Barlet test with Î±=0.05). Building on research result show that : (1) there are different the clear influence between massed practice learning and distributed practice learning, Fhitung =7.554 > Ftabel = 4.04. Distributed practice learning have better progress than at massed practice learning. (2) There are different of influence that significan between group who have good power arm muscle, medium, and less, Fhitung= 4.881> Ftabel= 3.18. The player having good power arm muscle who have progress ability badminton lob better than player who have medium power arm muscle or less. (3) Get on interaction between massed practice learning, distributed practice learning and power arm muscle, FHitung= 11.409 > FTabel = 3.19.